Cannabis, youth and social identity: the evolving meaning of cannabis use in adolescence. (21st October 2022) - Bilgrei, Ola Røed; Buvik, Kristin; Tokle, Rikke; Scheffels, Janne
ABSTRACT: This article explores the evolving meaning of cannabis use in adolescence. Based on longitudinal qualitative data from 50 focus-group and 175 individual interviews with young Norwegians, followed from the ages of 12–13 years to 16–17 years, the analysis shows how representations, opinions and use of cannabis gradually evolve. When first interviewed, none had personal experience with the drug and the students spoke of cannabis use as a symbol of addiction and marginalisation, linked to both individual and social problems. However, by the age of 16–17, one quarter of the sample had personal experience. The analysis highlights how the symbolic representations and associated identities of cannabis use change during adolescence – from repeating and exaggerating adult voices, the students gradually developed the symbolic imagery of cannabis use, based on influences from their peers, popular culture and the internet. As such, the associated meanings of cannabis use evolved from a distant phase, to a phase of negotiation that reflected their expanded cultural references during the years in question. The longitudinal design highlights how the symbolic meanings associated with cannabis use evolve over time, and how they play an important role in explaining both abstinence from and initiation to cannabis use.